Pengembangan E-Book Terintegrasi Pendekatan Contextual Teaching And Learning (CTL) pada Materi Struktur dan Fungsi Jaringan Tumbuhan untuk Meningkatkan Keterampilan Argumentasi dan Hasil Belajar Kognitif Siswa SMA - Damayanti, Alfiya; Kuswandi, Paramita. C. (Universitas Negeri Jakarta, 2024)
This research was motivated by obstacles in implementing biology learning which resulted in the lack of training in argumentation skills and low cognitive learning outcomes. The current teaching materials does not yet support these skills optimally. The aim of this research is to develop an e-book blending contextual teaching learning that is feasible, practical and effective to boost high school student’s argumentation and cognitive skills. A research and development method was used using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The subjects of this research were 34 high school students in Sleman, Yogyakarta in limited trials and 62 students in field trials. The type of research used in the field test was quasi-experimental with a pretest-post-test control group design. Class XI MIPA 1 was used as the control class and class XII MIPA 2 as the experimental class. Data collection instruments used included product assessment questionnaires by experts, biology teachers and students, argumentation skills and cognitive learning outcomes test instruments. Data analysis used the paired sample t-test, independent sample t-test and n-gain score test. The research results show that e-books is suitable for use in learning according to material experts and media experts, e-books is practical for use in learning according to teacher and student assessments, and e-books is effective for improving students' argumentation skills and learning outcomes. The conclusion in this research is that e-books blending contextual teaching and learning are feasible, practical and effective to use to boost students' argumentation and cognitive skills.